2007
DOI: 10.1016/j.amjhyper.2007.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25-hydroxyvitamin D, Ethnicity, and Blood Pressure in the Third National Health and Nutrition Examination Survey

Abstract: Vitamin D status, which is amenable to intervention by safely increasing sun exposure or vitamin D supplementation, was associated inversely with BP in a large sample representative of the US population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
312
7
18

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 499 publications
(368 citation statements)
references
References 27 publications
31
312
7
18
Order By: Relevance
“…20 Although we did not find any association between serum 25OHD and blood pressure, previous crosssectional studies 16,33 have documented an inverse relationship between serum 25OHD and blood pressure. In the cross-sectional analyses restricted to 12 644 people aged 20 years and above, mean (standard error) SBP was 3.0 (0.7) mm Hg lower (P ¼ 0.0004) and DBP was 1.6 (0.6) mm Hg lower (P ¼ 0.011) for participants in the highest quintile (25OHDX85.7 nmol l À1 ) compared with the lowest (25OHDo40.4 nmol l À1 ), after adjustment for age, sex, ethnicity and physical activity.…”
Section: -O76contrasting
confidence: 70%
See 3 more Smart Citations
“…20 Although we did not find any association between serum 25OHD and blood pressure, previous crosssectional studies 16,33 have documented an inverse relationship between serum 25OHD and blood pressure. In the cross-sectional analyses restricted to 12 644 people aged 20 years and above, mean (standard error) SBP was 3.0 (0.7) mm Hg lower (P ¼ 0.0004) and DBP was 1.6 (0.6) mm Hg lower (P ¼ 0.011) for participants in the highest quintile (25OHDX85.7 nmol l À1 ) compared with the lowest (25OHDo40.4 nmol l À1 ), after adjustment for age, sex, ethnicity and physical activity.…”
Section: -O76contrasting
confidence: 70%
“…These findings are supported by results of some observational studies, 31,32 but not the others. 16,21,33 In the Longitudinal Ageing Study Amsterdam, serum PTH rather than serum 25OHD was associated with SBP or DBP, or prevalence of hypertension in 1205 men and women aged 65 years and older after adjustment of potential confounders. 31 The result was consistent with that of the Ranch Bernardo Study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In vivo studies have shown that vitamin D deficiency leads to decreased insulin production from pancreatic β cells, leading to impaired glucose tolerance. In the Third National Health and Nutrition Examination Survey, lower vitamin D status was associated with higher fasting glucose and 2-hour glucose after oral glucose tolerance test [37]. In case-control studies in children, vitamin D supplementation has been protective against developing type 1 diabetes later in life [1••].…”
Section: Diabetesmentioning
confidence: 99%